Customer and Stakeholder Perspective using Analytical Hierarchy Process Method for Evaluation Performance of Higher Education - Satria Abadi; Setyawan Widyarto; Nur Syufizah Ahmad Shukor (International Journal of Supply Chain Management, 2019)
The measurement of the higher education performance is a complex issue and becoming increasingly important. Currently, performance measurements have been changed. It is no longer evaluated from the classical financial indicators. Instead, the customer satisfaction has been proposed as the basis for a management strategic within organizational. This paper presents performance measurement at the higher education concerning in customers and stakeholders perspective using the Analytic Hierarchy Process (AHP) method. AHP is a quantitative method which can deal with complicated decision-making problem for evaluation. Total of four main criteria and 26 sub-criteria were identified as significant to the customers and stakeholders perspective. This empirically finding is suggested to be a good performance measurement for solving the problem multi criteria and contributes strategic goal in higher education.